Sudden Unexplained Death and Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs)
The incidence of sudden unexplained death (SUD) among patients less than 50 years old with refractory epilepsy was determined at Boston University Medical Center, Lexington, MA, and Department of Epidemiology, Glaxo Wellcome, Research Triangle Park, NC.